Global status report on alcohol and health, 2014 (World Health Organization, 2014)
The Global status report on alcohol and health 2014 presents a comprehensive perspective on the global, regional and country consumption of alcohol, patterns of drinking, health consequences and policy responses in Member States. It represents a continuing effort by the World Health Organization (WHO) to support Member States in collecting information in order to assist them in their efforts to reduce the harmful use of alcohol, and its health and social consequences. The report was launched in Geneva on Monday 12 May 2014 during the second meeting of the global network of WHO national counterparts for implementation of the global strategy to reduce the harmful use of alcohol.--